Out of Bounds: A Visual Exploration of the Glitch - Goates, Thomas Miles (Curtin University, 2021)
This practice-led research aims to present a body of artwork that responds to glitches found in contemporary action video games. By utilising the visual capabilities of a virtual reality headset, I have produced a series of artworks that showcase the sensory effects that a glitch has on a player’s game world. The artwork that I have developed translates the materiality of traditional drawing into a digital space to visualise the qualities of glitches.